Peningkatan Efisiensi dan Keamanan parkir kendaraan dengan Integrasi KTM berbasis IoT - Fathur Andre Fadilah; Binastya Anggara Sekti (Prosiding SISFOTEK, 2024)
The research carried out includes analysis of the manual parking system previously used on campus and evaluation of the implementation of an IoT-based parking system with KTM integration. This research aims to solve problems caused by manual systems such as long queues, inaccurate recording and high security risks. By integrating IoT technology, this system is expected to increase work efficiency and parking safety. The research method used is a qualitative approach where information is collected through in-depth interviews, field observations and document analysis. Interviews were conducted with students, administrative staff and parking attendants. Field observations observe directly how this system is implemented and functions in field conditions. Document analysis is used to complement the information obtained from interviews and observations. The data collected shows that the IoT-based parking system with KTM integration significantly reduces the time needed to search for a parking space and speeds up entry and exit from the parking space. Users, including students, administrative staff, and parking attendants, are very positive about the system. They believe this system will facilitate access and increase the efficiency and safety of campus parking. The research results show that the IoT-based parking system with KTM integration has succeeded in increasing operational efficiency and parking safety at Esa Unggul University. The conclusion of this research is that the implementation of an IoT-based parking system integrated with KTM at Esa Unggul University has had a significant positive impact on parking efficiency and safety. The study also identified opportunities for further development, such as integration with digital payment systems and analysis of parking data to improve capacity planning.